The role of digital technologies for circular economy in the water sector - Yang, Longjian; Yang, Miying; Wu, Hongbin (Elsevier, 2026)
Circular economy offers a promising pathway to address the global water crisis, yet its application in the water sector remains fragmented. Over the past two years, rapid advances in digital technologies have begun to reshape circular water systems. This paper synthesises recent literature on how digital technologies could enable circularity across water systems. We propose a consolidated 7Rs framework tailored to the water sector under three areas: (i) minimising water use and waste (Reduce), (ii) optimising the value of water and wastewater (Redistribute, Reuse, Recycle and Recover) and (iii) maximising water resource generation (Restore, Regenerate). In particular, we highlight Regenerate as an emerging strategy focused on upgrading water quality for high-value applications. Our review shows that these circular strategies are rarely enabled by single technologies alone, but by integrated digital systems and their underlying functions. We identify ten key digital functions for water circularity and find that applications are most advanced in Reduce, Recycle and Recover, with Reduce representing a particularly accessible, high-impact strategy for practitioners. We also argue that digital technologies are no longer limited to efficiency improvements, but increasingly support system-level strategies for demand reduction, intelligent water redistribution, large-scale reuse and recycling. The review concludes by identifying key technological, economic and institutional conditions for adopting digital circular water systems and outlines priorities for future research.
Part of special issue: Accelerating Transition to Circular Economy in the Water Sector
Keywords: 4004 Chemical Engineering; 40 Engineering; 12 Responsible Consumption and Production; 6 Clean Water and Sanitation